A Combined Negative and Positive Enrichment Assay for Cancer Cells Isolation and Purification. (February 2016) - Cheng, Boran; Wang, Shuyi; Chen, Yuanyuan; Fang, Yuan; Chen, Fangfang; Wang, Zhenmeng; Xiong, Bin
Cancer cells that detach from solid tumor and circulate in the peripheral blood (CTCs) have been considered as a new "biomarker" for the detection and characterization of cancers. However, isolating and detecting cancer cells from the cancer patient peripheral blood have been technically challenging, owing to the small sub-population of CTCs (a few to hundreds per milliliter). Here we demonstrate a simple and efficient cancer cells isolation and purification method. A biocompatible and surface roughness controllable TiO2 nanofilm was deposited onto a glass slide to achieve enhanced topographic interactions with nanoscale cellular surface components, again, anti-CD45 (a leukocyte common antigen) and anti-EpCAM (epithelial cell adhesion molecule) were then coated onto the surface of the nanofilm for advance depletion of white blood cells (WBCs) and specific isolation of CTCs, respectively. Comparing to the conventional positive enrichment technology, this method exhibited excellent biocompatibility and equally high capture efficiency. Moreover, the maximum number of background cells (WBCs) was removed, and viable and functional cancer cells were isolated with high purity. Utilizing the horizontally packed TiO2 nanofilm improved pure CTC-capture through combining cell-capture-agent and cancer cell-preferred nanoscale topography, which represented a new method capable of obtaining biologically functional CTCs for subsequent molecular analysis.